Guide for Maintaining the Quality and Safety of Organic Vegetables and Melons During Harvest and Handling Operations - Steven A. Sargent; Danielle Treadwell (EDIS, 2009)
HS-1148, a 7-page fact sheet by Steven A. Sargent and Danielle Treadwell, highlights practical guidelines to assist growers and handlers of organic vegetables and melons to minimize losses during harvest and handling operations. Differences in recommendations between crops grown using organic methods and conventional production methods are noted. Includes references. Published by the UF Department of Horticultural Sciences, March 2009.